POLA PEMBINAAN MAHASISWA UKM LPM DINAMIKA DALAM PENINGKATAN KEMAMPUAN MENULIS DI UIN RADEN MAS SAID SURAKARTA - Fahrurrozi, Muhammad; Kautsar, Robith Thoriq Al (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the student development model implemented by UKM LPM Dinamika in enhancing writing skills at UIN Raden Mas Said Surakarta. The background of this research is grounded in the importance of academic literacy as a twenty-first-century competency and the low participation of students in writing activities and scientific publications. This research employs a descriptive qualitative approach with thematic analysis, following Krippendorff’s guidelines on content analysis and the qualitative data processing procedures outlined by Hardani et al. (2020). Primary data were obtained through an in-depth interview with the Chairperson of UKM LPM Dinamika, supported by a literature review related to literacy development and the enhancement of students’ writing capacity. The findings show that the development model consists of four core programs: the BRAIN Dinamika Basic Training as the foundation for research and writing skills; Routine Literacy Activities such as book and film discussions to cultivate reading habits and critical thinking; Writing Week as an intensive mentoring program for producing scientific papers; and the JAGOAN Achievement Program for coaching students in writing competitions. This development model significantly contributes to improving students’ writing abilities in terms of technical skills, argumentative structure, and academic confidence. These findings reinforce the strategic role of student-based literacy communities in strengthening the academic culture within the university environment.